The use of cinacalcet in pregnancy to treat a complex case of parathyroid carcinoma. - Nadarasa, K; Bailey, M; Chahal, H; Raja, O; Bhat, R; Gayle, C; Grossman, AB; Druce, MR (2014)
UNLABELLED: We present the case of a patient with metastatic parathyroid carcinoma whose hypercalcaemia was medically managed through two pregnancies. The diagnosis was made when the patient presented with chronic knee pain and radiological findings consistent with a brown tumour, at the age of 30. Her corrected calcium and parathyroid hormone (PTH) levels were significantly elevated. Following localisation studies, a right parathyroidectomy was performed with histology revealing parathyroid carcinoma, adherent to thyroid tissue. Aged 33, following biochemical recurrence of disease, the patient underwent a second operation. A subsequent CT and FDG-PET revealed bibasal pulmonary metastases. Aged 35, the patient was referred to our unit for treatment of persistent hypercalcaemia. The focus of treatment at this time was debulking metastatic disease using radiofrequency ablation. Despite advice to the contrary, the patient conceived twice while taking cinacalcet. Even though there are limited available data regarding the use of cinacalcet in pregnancy, both pregnancies continued to term with the delivery of healthy infants, using intensive medical management for persistent hypercalcaemia. LEARNING POINTS: Parathyroid carcinoma is a rare cause of primary hyperparathyroidism.Hypercalcaemia during pregnancy can result in significant complications for both the mother and the foetus.The use of high-dose cinacalcet in pregnancy has been shown, in this case, to aid in the management of resistant hypercalcaemia without teratogenicity.